Experimental Study of Erosion Threshold Shear Stress of Deposited Cohesive Sediments with Different Self-Weight Consolidation - Hossein Samadiborojeni; Nima Akbari; Behzad Ghorbani (علوم و مهندسی آبیاری, 2014)
Cohesive sediments are gradually consolidated after settling in dam reservoirs, settling ponds and channels. For hydraulic flushing of the sediments it’s necessary that the erosion threshold velocity and shear stress of these types of sediments to be known. In this study, by using the annular flume in Shahrekord University, this subject was investigated. Fine sediments used in the experiments, were collected from the reservoir bed of Pirbaloot earthfill dam located in north Karun basin, in Chaharmahal and Bakhtiari province. By conducting physicochemical tests the sediments properties were obtained. Five experiments to determine the erosion threshold of cohesive sediments with consolidation of five weeks, three weeks, two weeks, one week and three days was performed and velocity and shear stress of erosion threshold of sediments was measured by the ADV velocimeter. Results showed that erosion threshold of these sediments have a logarithmic relationship with the sediment consolidation time.  The amount of erosion threshold shear stress of sediments for surface sediments were obtained in a range of 0.12 to 0.14 N/m2 for sediment with difference age of self-weight consolidation. These values for subsurface sediments were obtained at 0.44 and 0.69 N/m2, respectively.